Analysing the Role of ChatGPT in Improving Student Productivity in Higher Education - Fauzi Fauzi; Laros Tuhuteru; Ferdinandus Sampe; Abu Muna Almaududi Ausat; Heliza Rahmania Hatta (Departement of Mathematics Education, 2023)
Student productivity in higher education is still a problem. In the digital era, technology is increasingly developing and provides convenience for doing various things, including in terms of learning. The purpose of this study will be an analysis of the role of ChatGPT in helping to improve the quality of student productivity. This research is qualitative in nature. Data collection techniques include listening and recording important information to conduct data analysis through data reduction, data display, and conclusion drawing. This study concludes that ChatGPT can make a significant contribution in improving the quality of student productivity. This language model can help students in various ways, such as providing useful information and resources, helping to improve language skills, facilitating collaboration, increasing time efficiency and effectiveness, and providing support and motivation.